HIGH PREVALENCE AND SEVERITY OF POSTPARTUM RETINOVASCULAR CHANGES FOLLOWING PRE- ECLAMPSIA WITH SEVERE FEATURES COMPARED TO NORMAL PREGNANCY. (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2017)
Background: Hypertensive retinopathy complicates about 40-100% of pregnancies with hypertensive  disorders and its severity worsens with progression of hypertension. Reactive retinal vessel changes demonstrably also mirror cardiovascular changes in the course of normal  pregnancy. There is low utility of fundoscopy in assessing target organ damage and prognosis in pre-eclampsia  in low resource setting.  Objective: To compare postpartum maternal retinovascular (RV) findings between pregnancies complicated  with preeclampsia with severe features (PES) and normal pregnancies at Kenyatta National Hospital (KNH). Methodology: Design: Comparative cross-sectional study conducted between May 2017 and March 2018. Setting: KNH, a regional Teaching and Referral hospital.  Study population: Sixty-five women within 72 hours postpartum without preexisting ocular or medical co morbidities following normal pregnancy (n=35) or pregnancies complicated with PES (n=30). Data collection: Participants were interviewed on sociodemographic and reproductive health characteristics  and clinical parameters obtained from medical records. Visual acuity assessment was done using a portable  LogMAR chart and non-mydriatic fundus photography used for retinovascular evaluation. RV changes were  graded using Keith Wagner grading. Data analysis: Postpartum retinovascular findings and severity grades were analyzed and presented as  percentages and compared between the two groups using Chi square or Fisher’s exact test. Odds ratios (OR)  of retinovascular changes following pre-eclampsia compared to normal pregnancy was estimated. A p value of